(untitled) (Al-Academy, 2026)
The visually impaired (the blind) is one of the categories of special education that need care according to their abilities in order to benefit from their energies as productive individuals in society, which contributes to achieving social integration. This means providing all means and opportunities for them to live a decent life in the environment in which their ordinary peers live. And everything that would facilitate their integration with their peers and those around them in the society in which they live. Due to the lack of a study that addressed the characteristics of artistic expression among blind students, which provided the researcher with justification for the necessity of research, the current research aims to identify the characteristics of artistic expression among blind students. The research community consisted of (40) male and female students, and (10) of them were chosen as a sample for the research. The researcher used the descriptive approach (content analysis method) because it is compatible with the goal of the research, and the research tool was prepared, which consisted of an analysis form. The researcher used statistical methods: the Cooper equation to find the percentage of agreement between the arbitrators, the Scott equation to calculate the validity of the tool, and the coefficient Pearson correlation to extract reliability using the split-half method. The most important results: In the field of the main paragraph (line quality), the two secondary paragraphs (curved and varied) obtained the highest percentage, reaching (70%). As for the main field (colors), the secondary section (colors are used thematically) received the highest percentage, reaching (90%). As for the most important conclusions: The art education teacher has a great impact in enabling blind students to artistically express what is inside them, use colors, use natural vocabulary, and curved lines. The researcher recommended paying attention to blind students.